Impacto da redução de pessoal sobre o trabalho e desempenho do sistema: experiência em uma subestação conversora de energia elétrica - Silva, Daniela Bainy da (2016)
This research analyzes the work of the operators of a converter substation of electricity from the interior, which can be considered exhausting due to the operating modes that are intrinsic in their daily lives. The objective seeks to identify the impacts caused by organizational changes on the work of people and the system performance due to reduced staff started in 2011. The methodology used was a case study outlined by the Activity Ergonomics of Work. The results indicated that before the staff reduction procedures were performed more safely and accompanied by aspects related to learning issues and recognition of operators. It was concluded that changes in work organization impacted in accelerating the scrapping of the equipment and the precariousness of the work of operators.